2009
DOI: 10.3164/jcbn.08-191
|View full text |Cite
|
Sign up to set email alerts
|

The Study on Long-Term Toxicity of D-Psicose in Rats

Abstract: D-Psicose is a rare sugar present in small quantities in natural products. In a previous study, we showed that D-psicose suppresses plasma glucose increases and reduces body fat accumulation in rats. Based on acute toxicity testing in rats, D-psicose is classified as an ordinary substance (LD50 = 16 g/kg). Elucidating the effects of long term feeding of D-psicose in rats will be essential prior to its utilization as a physiologically functional food. In this study, male Wistar rats (3 weeks old) were fed diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 23 publications
1
55
1
3
Order By: Relevance
“…In addition, kidney weight was significantly higher in the MGS group than in the RSS group. In our previous sub-chronic toxicity study using rats, administration of d-allulose at the level of 3% in the diet also showed weight gain of the liver and kidneys, but did not show any adverse health effects (29). Since, similar to d-tagatose, hepatic glycogen accumulation induced by d-allulose has been reported (10), enlarged liver is likely to be due to increased glycogen content.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, kidney weight was significantly higher in the MGS group than in the RSS group. In our previous sub-chronic toxicity study using rats, administration of d-allulose at the level of 3% in the diet also showed weight gain of the liver and kidneys, but did not show any adverse health effects (29). Since, similar to d-tagatose, hepatic glycogen accumulation induced by d-allulose has been reported (10), enlarged liver is likely to be due to increased glycogen content.…”
Section: Resultsmentioning
confidence: 99%
“…The rats were randomly divided into two groups of 10 (control and PS groups). We adopted Dpsicose as a control for PS because the safety of D-psicose was confirmed by our previous studies in animals and humans [11,[14][15][16]. The compositions of experimental diets are shown in Table 1.…”
Section: Animals and Experimental Dietsmentioning
confidence: 98%
“…We have examined the effects of acute [11], sub-chronic (90 days) [15], and long-term feeding (12 -18 months) [14] of D-psicose to rats prior to its utilization as a physiologically functional food. We concluded that a small amount of D-psicose in the diet had no adverse effects in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount test carbohydrate was decided by reference to previous studies of sucralose and D-psicose. 9,11) Body weight gain and food intake were recorded every day. After 6 months, the rats were fasted overnight from 22:00 h, and then sacrificed by exsanguinity under anesthetization with intraperitoneal sodium pentobarbital.…”
mentioning
confidence: 99%